EFEKTIVITAS TERAPI EMPATI UNTUK MENURUNKAN PERILAKU BULLYING PADA ANAK USIA SEKOLAH DASAR - Adinar Fatimatuzzahro; Miftahun Nimah Suseno; Bpk Irwanto (JURNAL PETIK, 2017)
This study aims to determine theeffectiveness of therapy in reducing bullyingbehavior empathy in primary school age childrenand to tackle issues of bullying behavior since basiceducation (elementary school) with empathytherapy. Subjects in this study were four studentsaged 10-12 years and had a propensity scorebullying of moderate to high. The design was onegroup pre - test- post-test. Collecting data in thisstudy was conducted using a scale of bullyingbehavior tendency with behavioral checklist modelprepared by the researcher. Data analysis methodsused by using techniques Wilcoxon Signed RankTest to test for differences in the data score pre test,post test and post test2 (follow up). Results of theanalysis score pre test-post test showed p value of0.001 and post test2 (follow up) p value of 0.002. Itcan be concluded that the therapy empathy iseffective in reducing the empathy bullying behaviorin children of primary school age